Rotavirus infection and histo-blood group antigens in the children hospitalized with diarrhoea in China. (August 2016) - Sun, X.; Guo, N.; Li, J.; Yan, X.; He, Z.; Li, D.; Jin, M.; Xie, G.; Pang, L.; Zhang, Q.; Liu, N.; Duan, Z.-J.
Abstract: To explore the association between rotavirus (RV) infection and histo-blood group antigens (HBGAs), a cross-sectional study was conducted in children hospitalized with diarrhoea in China from November 2014 to February 2015. In total, 424 sets of stool, saliva and buccal cell samples were collected. For the 125 RV-negative samples, 92% (104/125) were secretors/partial secretors, 8% (10/125) were non-secretors. Among the 299 RV-positive samples, 277 were P[8] and 22 were P[4]. All P[4] and P[8] positive individuals were secretors/partial secretors except for one P[8] (0.3%, 1/299), which was a non-secretor. These findings indicate that P[8] and P[4] RVs preferably infect secretors/partial secretors (p <0.001).